Control of gas phase nanoparticle shape and its effect on MRI relaxivity. (17th February 2015) - Aktaş, S𝚤tk𝚤; Thornton, Stuart C; Binns, Chris; Lari, Leonardo; Pratt, Andrew; Kröger, Roland; Horsfield, Mark A
Abstract: We have used a sputtering gas aggregation source to produce Fe@FeO nanoparticles with different shapes, by annealing them at different temperatures in the gas phase. Without annealing, the most common shape found for the nanoparticles is cubic but annealing the nanoparticles at 1129 °C transforms the cubes into cuboctahedra. Measurements of the MRI relaxivity show that the cubic nanoparticles have a higher performance by a factor of two, which is attributed to a higher saturation magnetization for this shape. This indicates that the shape-control enabled by gas-phase synthesis is important for obtaining optimal performance in applications.